Improved localization of language areas using single voxel signal analysis of unprocessed fMRI data - Fetscher, Leonard; Batra, Marion; Klose, Uwe (Frontiers in Radiology, 2022)
Activated brain regions can be visualized and localized with the use of fMRI (functional magnetic imaging). This is based on changes in the blood flow in activated regions, or more precisely on the hemodynamic response function (HRF) and the Blood-Oxygen-Level-Dependent (BOLD) effect. To stimulate the language areas, this study used a task-based fMRI examination with language paradigms. For the analysis and display of activations, the measured fMRI data are frequently altered by different preprocessing steps. These changes can lead to discrepancies between the displayed and the truly measured location of the activations. In this study, simple t-maps were created with unprocessed fMRI data, to provide a more realistic representation of the language areas. To improve the analyzability of these activation maps, HRF-dependent single-voxel fMRI signal analysis was performed.